Embedded type sewage-treatment control device - XU LINGHUA; PAN SHENGGUI; CAO LEI; LI HANDONG (2011)
The utility model discloses an embedded type sewage-treatment control device. The device comprises a central processor (1), an external memory (2), a joint test action group (JTAG) interface, a serial interface, a touch screen (3), a sewage-treatment equipment interface and a sewage parameter collection interface, wherein the central processor (1) is respectively connected with a conversion interface (5) of an analog/digital converter, a conversion interface (4) of a digital/analog converter, the external memory (2) and the touch screen (3); the conversion interface (5) of the analog/digital converter is also connected with a frequency-conversion controller (6) and then is connected with the external sewage-treatment equipment interface; and the conversion interface (4) of the digital/analog converter is also connected with a chemical oxygen demand collection interface (9), a biochemical oxygen demand collection interface (8) and a liquid level parameter collection interface (7). The device has the advantages